Anticholinergic burden in the Japanese elderly population: Use of antimuscarinic medications for overactive bladder patients. (1st August 2018) - Yoshida, Masaki; Kato, Daisuke; Nishimura, Takuya; Van Schyndle, James; Uno, Satoshi; Kimura, Tomomi
Abstract : Objectives: To assess anticholinergic use, especially the use of antimuscarinics, in the elderly (aged ≥65 years) Japanese overactive bladder and non‐overactive bladder populations. Methods: Patient records were sourced from a large, nationwide Japanese pharmacy claims database. Anticholinergic use on a random day in 2016 (index date) was investigated through the Anticholinergic Cognitive Burden scale (primary scale), the Anticholinergic Drug Scale, the Anticholinergic Risk Scale and Beers criteria. The prevalence of anticholinergic use and anticholinergic scores at the index date were summarized descriptively. The overactive bladder population was defined as patients who had at least one prescription record for any antimuscarinic (fesoterodine, imidafenacin, oxybutynin, propiverine, solifenacin or tolterodine) or the β3‐adrenoreceptor agonist, mirabegron, within the 1‐year pre‐index period. Results: Among 1 216 126 outpatients, 35 138 (2.9%) were included in the overactive bladder group. In total, 112 (68.7%) of the anticholinergics listed in the scales were identified. In those who received any Anticholinergic Cognitive Burden scale‐listed anticholinergic, the mean scores were higher in overactive bladder patients versus non‐overactive bladder patients (3.2 ± 1.3 and 1.6 ± 1.1, respectively). Similarly, overactive bladder patients who received antimuscarinics had higher Anticholinergic Cognitive Burden scores (3.3 ± 1.2) than patients who received mirabegron only (1.7 ± 1.1). In 58.8% of the overactive bladder patients, ≥80% of the total Anticholinergic Cognitive Burden score was exclusively attributable to antimuscarinics. Conclusions: Anticholinergic use was higher in overactive bladder patients versus non‐overactive bladder patients. This increased use was largely attributable to antimuscarinics. The alternative use of mirabegron could therefore be considered to reduce the burden experienced by patients in Japan.